2013
DOI: 10.1016/j.ultsonch.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Interaction behaviors at the interface between liquid Al–Si and solid Ti–6Al–4V in ultrasonic-assisted brazing in air

Abstract: Power ultrasonic vibration (20 kHz, 6 μm) was applied to assist the interaction between a liquid Al-Si alloy and solid Ti-6Al-4V substrate in air. The interaction behaviors, including breakage of the oxide film on the Ti-6Al-4V surface, chemical dissolution of solid Ti-6Al-4V, and interfacial chemical reactions, were investigated. Experimental results showed that numerous 2-20 μm diameter-sized pits formed on the Ti-6Al-4V surface. Propagation of ultrasonic waves in the liquid Al-Si alloy resulted in ultrasoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(36 citation statements)
references
References 57 publications
1
34
0
1
Order By: Relevance
“…Using USV for a short period results in very fast destroying of the oxide layer on the parent material and wetting it by the filler material [52], even it is effective in achieving a good wetting on ceramics by the filler materials in the air [53,54,62]. e acoustic cavitation generated in the liquid metal is considered as the most important physical effect of the ultrasonic oscillation propagation [63][64][65][66].…”
Section: Ultrasound-assisted Brazing Of Ti By Al-basedmentioning
confidence: 99%
See 3 more Smart Citations
“…Using USV for a short period results in very fast destroying of the oxide layer on the parent material and wetting it by the filler material [52], even it is effective in achieving a good wetting on ceramics by the filler materials in the air [53,54,62]. e acoustic cavitation generated in the liquid metal is considered as the most important physical effect of the ultrasonic oscillation propagation [63][64][65][66].…”
Section: Ultrasound-assisted Brazing Of Ti By Al-basedmentioning
confidence: 99%
“…e advantages include less specific atmosphere requirements due to the fast-breaking of the oxide layer [39,52], enhanced spreading of the molten filler [55,62], and homogenizing the microstructures of the joint [39]. Table 3 summarizes the technological parameters and the shear strength results of the ultrasound-assisted brazing of Ti/Ti and Ti/Al joints using Al-based fillers.…”
Section: Ultrasound-assisted Brazing Of Ti By Al-basedmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research works on the joining of Ti/Al have been reported [3,4,[7][8][9]. Some conventional fusion welding methods are not suitable for joining Ti/Al.…”
Section: Introductionmentioning
confidence: 99%